Opportunities for science centers and museums to cultivate a culture of climate action - Rose Hendricks; Theresa A. Donofrio (npj Climate Action)
Science centers and museums are uniquely positioned to spark climate action. In this commentary, we describe opportunities to further increase the field’s impact through research on the psychological states that drive action and public engagement approaches for sparking those states. We also introduce Seeding Action, an initiative led by the Association of Science and Technology Centers to address the opportunities for cross-museum research and coordination.